Europeanisation and new patterns of governance in Ireland : None - Rees, Nicholas (Book collections on Project MUSE., 2009)
This title examines how Europeanisation affected Irish policy-making and implementation and how Ireland maximised the policy opportunities arising from membership of the EU while preserving embedded patterns of political behaviour.